CONTINUOUS SPIRITUAL EDUCATION OF FUTURE TEACHERS THEORETICAL AND METHODOLOGICAL BASIS OF IMPROVING THE SYSTEM OF PREPARATION FOR THE EDUCATIONAL PROCESS (Scientific journal of the Fergana State University, 2023)
In this article, opinions on increasing the activity of introducing educational standards based on a new approach to the training of future physical education teachers, on awakening a sense of responsibility for the chosen profession, on the development of various reforms in society are presented.